The use of corporate annual reports by individual shareholders in Singapore. - Ng, Bee In. (2008)
In this paper, an attempt was made to study the use of annual reports by individual shareholders in Singapore. It is important for the accounting profession to understand the information needs of shareholders in making investment decisions in order to enhance the informativeness of annual reports.